Transport implementation of the Bernstein–Vazirani algorithm with ion qubits - S D Fallek; C D Herold; B J McMahon; K M Maller; K R Brown; J M Amini (New Journal of Physics, 2016)
Using trapped ion quantum bits in a scalable microfabricated surface trap, we perform the Bernstein–Vazirani algorithm. Our architecture takes advantage of the ion transport capabilities of such a trap. The algorithm is demonstrated using two- and three-ion chains. For three ions, an improvement is achieved compared to a classical system using the same number of oracle queries. For two ions and one query, we correctly determine an unknown bit string with probability 97.6(8)%. For three ions, we succeed with probability 80.9(3)%.